Analysis of Determinants of Employee Engagement in the Creative Industries Sector Located in North Sumatra - Indajang, Kevin; Efendi, Efendi; Andronicus, Melkyory; Putra, Loist Abdi; Sudirman, Acai (JURISMA : Jurnal Riset Bisnis & Manajemen, 2024)
The primary goal of this study is to examine how employee engagement in North Sumatra's creative industries sector is impacted by ethical leadership, self-efficacy, work-life balance, and perceived organizational support. The Purposive Sampling Technique was applied in this study. The sample's features include having more than a year of experience in a comparable role and not being an outsourced worker or a third party employed by the creative industry, which employs 210 people in total. The study's findings support the notion that work-life balance, self-efficacy, ethical leadership, and perceived organizational support all significantly and favorably impact employee engagement. The study's findings support the notion that work-life balance, self-efficacy, ethical leadership, and perceived organizational support all significantly and favorably impact employee engagement. According to this study, a comprehensive strategy that incorporates elements of moral leadership, self-assurance, work-life balance, and organizational support can successfully raise employee engagement in North Sumatra's creative industry sector.